Neuromodulation in primary headaches: current evidence and integration into clinical practice. Issue 3 (June 2020) - Rimmele, Florian; Jürgens, Tim P.
Abstract : Purpose of review: Neuromodulatory approaches add to our armamentarium of therapeutic tools for the treatment of primary headaches. This review provides a comprehensive overview of current controlled studies on the different neuromodulation techniques and recommendations for clinical practice. Recent findings: Evidence for efficacy of transcutaneous vagal nerve stimulation (tVNS) is limited to acute use in migraine with ambiguous results and episodic cluster headache as well as chronic cluster headache if applied in addition to conventional treatment. Transcutaneous stimulation of the supraorbital and supratrochlear nerve was effective in both acute and preventive stimulation (the latter with ambiguous results) in episodic migraines. Thus, invasive procedures should be reserved for severe and refractory cases only. Occipital nerve stimulation for chronic refractory cluster headache is the only available invasive approach with a Conformité Européenne mark. Summary: Neuromodulation can complement conventional therapy, with noninvasive procedures being used preferably. Given the limited number of studies for each modality and the lack of head-to-head studies, it is difficult to place neuromodulation techniques in a conventional treatment algorithm.